Historical Burial Site of the Pamanoekan en Tjiasemlanden (P&T Land) Era in Kampung Tengger Agung - Emiliawati, Emil; Welsi Damayanti (Universitas Negeri Semarang, 2024)
This research aims to find out the history of the tombs of Maria Elisabeth van Lawick Van Bast and Francis Theodorus Hofland in Tengger Agung, and to find out the differences in the condition of these tombs in prehistoric and present times. This research was carried out using historical methods through heuristics, namely by collecting information from historical sources, observation, documentation, and interviews with residents in Tengger Agung. The results of this research show that in Tengger Agung, Peter William Hofland founded the company P&T Land, and Pusara was owned by the wife and children of Johannes Theodorus Hofland, who was the second child of PW Hofland, owner of P&T Land. The current condition of the tomb is that the statue that used to be perched on top of the tomb has disappeared somewhere. The structure at the edge of the tomb is damaged, the fence and stairs around the tomb are out of shape and destroyed. With this research the author hopes that the results of this research can be used as material for further research to be able to find out more deeply about the history of Subang, and one of them is because Subang is one of the historical areas in the West Java region.